2016
DOI: 10.1007/s13730-016-0239-9
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal cell carcinoma with undetectable renal mass presenting as lymphadenopathy

Abstract: Renal cell carcinoma has the ability to metastasize to any organ; about 16 % of affected patients present initially with metastasis. However, it is rare for this tumor to present with metastasis from an unidentified primary. The current use of immunohistochemistry and molecular genetics has enabled clinicians to reach a precise diagnosis. It has been hypothesized that the treatment protocol for metastatic renal cell carcinoma can be applied to cases with undetectable primary. In this paper, a novel case of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
(24 reference statements)
0
7
0
4
Order By: Relevance
“…Renal cell carcinoma is the most common malignant tumor of the kidney, accounting for almost 3% of all human malignancies ( 1 ). Insensitivity to radiotherapy and chemotherapy are a great obstacle for the treatment of metastatic renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma is the most common malignant tumor of the kidney, accounting for almost 3% of all human malignancies ( 1 ). Insensitivity to radiotherapy and chemotherapy are a great obstacle for the treatment of metastatic renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Seven patients had surgery to treat a solitary metastatic lesion, with no additional systemic treatment provided. 8,9,11,[15][16][17] Eleven patients described in 8 case reports received targeted therapies with sunitinib (n ¼ 6), 6,7,10,18,19 pazopanib (n ¼ 2), 14,19 temsirolimus (n ¼ 2), 12 and everolimus (n ¼ 1). 13 Efficacy data showed that 8 (72%) of 11 patients responded to treatment, and 9 (82%) of 11 were alive when the cases were reported, surviving between 6 weeks and 36 months.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the above-mentioned case reports used molecular diagnostic tools after inconclusive IHC diagnostic assessment and identified the tissue of origin, thereby enabling treatment with TT. 10,[12][13][14]19 Molecular profiling is not yet part of standard diagnostic assessment at most institutions. 1 It is unknown why the primary tumor was not found in the kidneys at the time of diagnosis.…”
Section: Anders Overby Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…В литературе этому вопросу посвящены ограниченные сообщения в виде описания единичных случаев [8][9][10][11][12][13]. Локализация метастазов при этом весьма разнообразна.…”
Section: Introductionunclassified